2019
DOI: 10.1016/j.ebiom.2019.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of resistance mechanisms to abivertinib, a third-generation EGFR tyrosine kinase inhibitor, in patients with EGFR T790M-positive non-small cell lung cancer from a phase I trial

Abstract: Background Resistance to third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) presents a major clinical challenge in advanced non-small cell lung cancer (NSCLC). Here, we report resistance mechanisms to abivertinib, a novel third-generation EGFR TKI, from a phase I dose-escalation/expansion study ( NCT02330367 ). Methods Patients with EGFR T790M-positive advanced NSCLC and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 29 publications
(57 reference statements)
3
38
0
Order By: Relevance
“…Thus, the clinically significant benefit from subsequent treatment with osimertinib among our patients implies that abivertinib progression may be due to incomplete target inhibition, and the efficacy of abivertinib seemed weaker than that of osimertinib. The report by Zhang et al . showed that EGFR T790M loss (15%) with abivertinib resistance was much less frequent than that reported in osimertinib resistance cohorts (42%–68%), which verified the incomplete inhibition of abivertinib compared with osimertinib and also explained our findings regarding the response to osimertinib after abivertinib progression.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Thus, the clinically significant benefit from subsequent treatment with osimertinib among our patients implies that abivertinib progression may be due to incomplete target inhibition, and the efficacy of abivertinib seemed weaker than that of osimertinib. The report by Zhang et al . showed that EGFR T790M loss (15%) with abivertinib resistance was much less frequent than that reported in osimertinib resistance cohorts (42%–68%), which verified the incomplete inhibition of abivertinib compared with osimertinib and also explained our findings regarding the response to osimertinib after abivertinib progression.…”
Section: Discussionsupporting
confidence: 84%
“…also reported the resistance mechanisms to abivertinib according to next‐generation sequencing (NGS)‐based genomic profiling of the plasma samples of 27 patients who developed abivertinib progression from the phase I dose‐escalation/expansion study. Their findings also reveal a heterogenous pattern of resistance mechanisms to abivertinib that is distinct from that previously reported with osimertinib, and EGFR amplification was the most common resistance mechanism in their cohort …”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Acquisition of resistance to erlotinib was associated with the emergence of the EGFR T790M mutation, which has been linked to focal amplification of EGFR . 36 Analysis of the sequential ctDNA samples showed that this subclone was first sensitive to second-line EGFR TKI treatment, as indicated by disappearance of the EGFR T790M mutation. This mutation was detected again in ctDNA samples after SCLC transformation, but not in the second tumor biopsy, possibly due to proliferation of EGFR T790M -positive NSCLC cells at a metastatic site.…”
Section: Discussionmentioning
confidence: 99%